2010
DOI: 10.1128/jvi.01394-10
|View full text |Cite
|
Sign up to set email alerts
|

Tetrameric Ring Formation of Epstein-Barr Virus Polymerase Processivity Factor Is Crucial for Viral Replication

Abstract: The Epstein-Barr virus BMRF1 DNA polymerase processivity factor, which is essential for viral genome replication, exists mainly as a C-shaped head-to-head homodimer but partly forms a ring-shaped tetramer through tail-to-tail association. Based on its molecular structure, several BMRF1 mutant viruses were constructed to examine their influence on viral replication. The R256E virus, which has a severely impaired capacity for DNA binding and polymerase processivity, failed to form replication compartments, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Primer sequences used were as follows: for interleukin-8 (IL-8), 5=-CAA ACC TTT CCA CCC CAA AT-3= (forward) and 5=-CTC TGC ACC CAG TTT TCC TT-3= (reverse); for intercellular adhesion molecule 1 (ICAM-1), 5=-CAA CCG GAA GGT GTA TGA AC-3= (forward) and 5=-CAG CGT AGG GTA AGG TTC-3= (reverse); for AGT, 5=-GGA TGA GAG AGA GCC CAC AG-3= (forward) and 5=-CTC ACT CCA TGC AGC ACA CT-3= (reverse); for CCL2, 5=-CAT TGT GGC CAA GGA GAT CTG-3= (forward) and 5=-CTT CGG AGT TTG GGT TTG CTT-3= (reverse); and for GAPDH, 5=-GGG AAG GTG AAG GTC GGA GT-3= (forward) and 5=-AAG ACG CCA GTG GAC TCC AC-3= (reverse). Quantification of viral DNA synthesis during lytic replication was essentially conducted as described previously (44).…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences used were as follows: for interleukin-8 (IL-8), 5=-CAA ACC TTT CCA CCC CAA AT-3= (forward) and 5=-CTC TGC ACC CAG TTT TCC TT-3= (reverse); for intercellular adhesion molecule 1 (ICAM-1), 5=-CAA CCG GAA GGT GTA TGA AC-3= (forward) and 5=-CAG CGT AGG GTA AGG TTC-3= (reverse); for AGT, 5=-GGA TGA GAG AGA GCC CAC AG-3= (forward) and 5=-CTC ACT CCA TGC AGC ACA CT-3= (reverse); for CCL2, 5=-CAT TGT GGC CAA GGA GAT CTG-3= (forward) and 5=-CTT CGG AGT TTG GGT TTG CTT-3= (reverse); and for GAPDH, 5=-GGG AAG GTG AAG GTC GGA GT-3= (forward) and 5=-AAG ACG CCA GTG GAC TCC AC-3= (reverse). Quantification of viral DNA synthesis during lytic replication was essentially conducted as described previously (44).…”
Section: Methodsmentioning
confidence: 99%
“…BZLF1 has been reported to interact with the viral helicase -primase complex (Table 1) (Liao et al 2001(Liao et al , 2005El-Guindy et al 2010) and the viral polymerase accessory factor BMRF1 (Takagi et al 1991;Daikoku et al 2005;Nakayama et al 2009). BMRF1 bears structural similarities with cellular PCNA Nakayama et al 2010) and could potentially provide an additional tethering function for the replication complex (Zhang et al 1997;Baumann et al 1999). In addition, the primase-associated factor might serve a similar tethering function in conjunction with cellular, oriLyt-binding proteins (see below and Liao et al 2005).…”
Section: Proteins That Support the Functions Of Orilytmentioning
confidence: 99%
“…Three different classes of EBV genes have been characterized, the immediate-early (IE), early (E), and late (L) genes (16). The switch from latent to lytic infection is triggered by expression of the IE BZLF1 gene product, a b-Zip transcriptional factor (15,17,18). The BZLF1 protein binds to the promoters of E genes encoding proteins involved in viral DNA replication and metabolism (19,20) and recruits RNA polymerase II on their promoters (21), initiating the lytic cascade program.…”
mentioning
confidence: 99%
“…BMRF1 is a major phosphoprotein abundantly expressed during EBV productive infection (11,12) which forms a heterodimer with the BALF5 polymerase catalytic subunit to enhance polymerase processivity (13). Furthermore, crystal structure analysis has demonstrated that BMRF1 by itself forms head-to-head homodimer or tetrameric ring structures (14,15), presumably contributing to BMRF1 core structures. Thus, the BMRF1 protein may play dual roles during lytic replication, one as a polymerase processivity factor and the other in protecting the viral genome after synthesis.…”
mentioning
confidence: 99%